Aproveitamento dos resíduos sólidos urbanos do município de Tucuruí para geração de energia elétrica - SILVA, Gabriele Ferreira Fiel e (2024)
The closure of dumping ground and the energy use of waste are environmental issues of great relevance today, especially given the challenges related to the sustainable management of solid waste and the search for more efficient and environmentally appropriate alternatives. The present study aims to encourage the closure of the open dump area in Tucuruí – Pará, for the purpose of complying with the National Solid Waste Policy, and to estimate the energy potential through the use of solid waste (SW) disposed in the area. The methodology consisted of a bibliographical survey of solid waste management in Tucuruí. Then, two energy generation routes were applied to take advantage of the area's RS, from the implementation of a sanitary landfill, route 1 (landfill and landfill biogas capture) and route 2 (recycling, anaerobic digestion and landfill). The results showed route 2 as the most efficient, with an estimated generation of 36,204,192 kWh/year. This total would supply 10,057 low-income homes. Furthermore, the use would avoid 19,110.89 tons of methane (CH4), the equivalent of 401,328.69 tons of carbon dioxide (CO2) in the atmosphere, thus reducing greenhouse gases (GHG), in addition to meeting the Development Objectives Sustainable (SDG). This work also reinforces the social and economic inclusion of recyclable material collectors, reduction of negative health impacts resulting from inadequate waste disposal, prevention of soil and water contamination, production of clean energy and encouragement of the circular economy.